Sex differences in a double-blind randomized clinical trial with minocycline: pilot findings on the key role of the immune system in treatment-resistant depressed female patients. (September 2021) - Lombardo, Giulia; Nettis, Maria Antonietta; Hastings, Caitlin; Zajkowska, Zuzanna; Mariani, Nicole; Nikkheslat, Naghmeh; Worrell, Courtney; Enache, Daniela; McLaughlin, Anna; Kose, Melisa; Sforzini, Luca; Bogdanova, Anna; et al.
Abstract : Background: The Minocycline in Depression (MINDEP) study is a 4-weeks double-blind, placebo-controlled clinical trial, investigating the efficacy of minocycline in treatment resistant depressed (TRD) patients with major depressive disorder, and C-reactive protein (CRP) ≥ 1 mg/L. Methods: We explored sex differences in the effects of study arms and CRP groups (CRP ≥ 3 mg/L; CRP < 3 mg/L) on HAMD-17 variation from baseline to week-4. Results: Independent samples t-test detected a significant difference between minocycline (M) and placebo (PL) groups only in males but not females, with M group (N=8) showing greater improvement in comparison with PL group (N=9) (p=0.046). However, M female group with CRP ≥ 3 mg/L (N=3) showed the greatest clinical improvement in comparison with the other female groups (p<0.05 vs. all groups). General linear model univariate analysis confirmed the significant interaction between study arms and CRP groups in females (p=0.005). Conclusion: These pilot findings suggest that TRD male patients may benefit from minocycline add-on treatment independently of their baseline inflammatory levels, while TRD female patients may benefit from minocycline only if having higher baseline inflammatory levels.